PENGARUH CORPORATE GOVERNANCE (DEWAN DIREKSI, DEWAN PENGAWAS SYARIAH, KOMITE AUDIT, DAN DEWAN KOMISARIS) TERHADAP KINERJA KEUANGAN (Studi Empiris pada Bank Umum Syariah di Indonesia yang Terdaftar di OJK Tahun 2021-2023) - Devi Alya Rahmatika; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This academic work intends to collect observable proof regarding the influence of the Board of Directors, the Number of Audit Committees, the Audit Committee Meetings, the Number of Sharia Supervisory Boards, the Sharia Supervisory Board Meetings, the Number of the Board of Commissioners, Independent Commissioner and the Board of Independent Commissioners on the financial performance of Islamic banks registered with the Financial Services Authority. Analyzes and data of the study uses a quantitative approach. Data was collected using secondary time series data, namely Islamic commercial banks officially registered with the OJK that publish complete and accessible annual financial reports from the 2021-2023 period. Hypothesis tests include determination coefficient tests, t tests and F tests. The results of this study prove that there is an influence of the Board of Directors on financial performance, There is no influence of the Number of Audit Committee on financial performance, There is no influence of the Audit Committee Meeting on financial performance, There is no influence of the Number of Sharia Supervisory Board on financial performance, There is no influence of the Sharia Supervisory Board Meeting on financial performance, There is an influence of the Board of Commissioners on financial performance, and simultaneously there is an influence of the variables of the Board of Directors, the Number of Audit Committees, the Audit Committee Meetings, the Number of Sharia Supervisory Boards, the Sharia Supervisory Board Meetings and the Board of Commissioners on financial performance.